Advances in artificial intelligence : 18th Conference of the Spanish Association for Artificial Intelligence, CAEPIA 2018, Granada, Spain, October 23-26, 2018, Proceedings /: 18th Conference of the Spanish Association for Artificial Intelligence, CAEPIA 2018, Granada, Spain, October 23-26, 2018, Proceedings. (2018) - Unknown
No abstract available